O alinhamento entre planejamento e execução orçamentária na Universidade Federal do Pampa no período de 2008 a 2018 - Roscoff, Renan Kaizer dos Santos (2020)
This study aimed to analyze the alignment between budget planning and execution at the Federal University of Pampa in the period 2008-2018, through a quantitative and qualitative study, using the analysis of data from government systems and semi-structured interviews. From the analysis of the institution's budget data, the evolution of the total budget and the most representative Expense Natures was verified, considering the categories of costing and capital. As a criterion for choosing expenses, it were considered, specifically, the Expense Natures that presented greater representativeness within the university's total budget during the analyzed period. Moreover, from an intentional non-probabilistic sampling, primary data were collected, through semi-structured interviews with managers who work or worked in the university’s planning and management departments. The results showed significant distortions in the budgetary-financial alignment of UNIPAMPA's expenses, both for the group of Other Current Expenses and the group of Investments. Such distortions were analyzed and ratified by the analysis of the interviews, making it possible to identify external and internal factors that contributed to the studied problem. Among the internal factors, the inefficiency of the expenses forecasting processes, the lack of coordination between the academic and administrative areas, the lack of communication between the planning and budget execution departments and the sparse structure of the university stand out. External factors include contingencies during the year and during the preparation of the Annual Budget Law Project; the release of funds at inopportune moments; the lack of updates for the laws that rules planning and budget of public agencies; the incompatibility of the accounting year’s period with teaching activities; and the length of the Annual Budgetary Law elaboration period. From these results, it was concluded that there is a great need and space for improvements in the budgetary-financial alignment of UNIPAMPA’s main expenses, since these distortions hinder the proper performance of the institution's activities and can directly reflect on the academic community. Likewise, it is extremely necessary for the Federal Government to adopt a clear policy for public universities.